Deportation limbo - Lindberg, Annika (Manchester University Press, 2023)
Deportation limbo traces the efforts of two Nordic welfare states, Denmark and Sweden, to address the so-called implementation gap in deportation enforcement. It offers an original, empirically grounded account of how often-futile, injurious policy measures devoted to pressuring non-deported people to leave are implemented and contested in practice. In doing so, it presents a critique of the widespread, normalised use of detention, encampment, and destitution, which routinely fail to enhance deportations while exposing deportable people to conditions that cause their premature death. The book takes the ‘deportation limbo’ as a starting point for exploring the violent nature of borders, the racial boundaries of welfare states, and the limits of state control over cross-border mobility. Building on unprecedented access to detention and deportation camps and migration offices in both countries, it presents ethnographic material capturing frontline officials’ tension-ridden efforts to regulate non-deported people using forced deportation, incarceration, encampment, and destitution. Using a continuum of state violence as the analytical lens, the book offers a uniquely comprehensive account of how the borders of Nordic welfare states are drawn through practices that subject racialised ‘others’ to expulsion, incarceration, and destitution. The book is the first to systematically document the renewed deportation turn in Denmark and Sweden, and to critically examine its implications: for the people targeted by intensified deportation measures, and for the individual officials, institutions, and societies enforcing them. It offers an important, critical contribution to current debates on the violence of deportation regimes, the politico-bureaucratic structures and practices that sustain them, and their human costs.